Kawasaki Disease - Hedrich, Christian M.; Schnabel, Anja; Hospach, Toni (Frontiers in Pediatrics, 2018)
Kawasaki disease (KD) is an acute-onset systemic vasculitis of medium-sized ves-sels that mostly affects infants and toddlers. Globally, it is the most common form of childhood primary vasculitis. Delayed diagnosis and treatment results in coronary artery aneurysms in up to 25% of all affected individuals. Thus, KD is the most com-mon acquired heart disease in developed countries. Here, the current under-standing of clinical presentations, pathophysiological concepts, disease-associated complications, and available pharmaceutical treatment is provided and discussed in the context of available literature.